Printing Conflicts in the Middle East (Political Geographic Review) - Manvender Singh (GoAcademica Research & Publishing, 2020)
MiddleEastis aregionwithgeographicalirony. With strong geographicelements and having both physical and non-physical diversepotentials, this region shouldbe politicallypowerful. In fact, Middle East seems like